MENGURAI KERANCUAN KONSEPTUAL VISUAL BASIC DAN VISUAL BASIC FOR APPLICATIONS PADA SISWA SMK PGRI 1 CIMAHI - Shandy Tresnawati; Ari Sudrajat; Reni Raafidiani; Nia Ekawati (PUAN INDONESIA, 2026)
This community service (PKM) initiative addresses the conceptual confusion among eleventh-grade students at SMK PGRI 1 Cimahi regarding the differences between Visual Basic (VB) and Visual Basic for Applications (VBA). This tumpangsari or overlap in understanding hindered their efficiency in advanced visual programming and automated data processing. To resolve this issue, a half-day interactive seminar and semi-workshop were conducted for 36 active students. The program combined theoretical insights on the distinct purposes, environments, and functions of VB and VBA with hands-on practices, such as activating the Excel Developer tab. Evaluation via Quizizz confirmed that students successfully acquired the technical skills to distinguish and utilize both platforms. Beyond technical competencies, the session enhanced students' digital literacy, cybersecurity awareness, and professional communication ethics. Ultimately, this initiative successfully fulfilled the Tri Dharma Perguruan Tinggi and fostered essential digital readiness for the students' upcoming internship programs.